Periodische Seespiegelschwankungen und ihre Auswirkungen auf die Agrarwirtschaft im Faguibine-See (Republik-Mali) - Krings, Thomas (ERDKUNDE, 1985)
Lake Faguibine in the Sahel of Mali (District of Timbuktu) is the most northerly link of a lake-chain (Tele, Faguibine, Gouber, Kamango) on the left side of the Niger River. The lakes are fed from the annual Niger flood by two natural channels (marigot of Tassakant and of Katoua). The flood maximum, which arrives at Dire in October/November, reaches the Tele and Faguibine Lake whith a delay of 1 1/2 months. The basins, separated by rocky shelves, are filled by decantation one after another. After the Niger recedes flood water remains in the lakes and water losses occur only through the high evaporation rates and lateral percolation. The long standing cyclical and annual variations of the lake-levels have most important effects on the position, extension and quality of the cultivated areas in the basin. Agriculture is mainly based on the utilisation of thewater resources led by the Niger flood. After the water recedes through evaporation arable land appears from the surrounding edges of the basin. Periods in which Lake Faguibine remains wholly filled throughout the year have negative effects for the cultivators, because very little land is available, whereas periods of low lake level are quite favourable for agriculture. In this case the most fertile clay soils in the eastern middle part can be cultivated with sorghum, millet, rice, wheat, maize, beans, sweet potatoes, okra and water-melons. In periods when the lake is drying out (as in1983) the agricultural situation changes completely. The arable land shifts from the western parts of the Lake and from the edges to the east-central parts where the best clay soils are sedimented. At the present time (1983) sorghum is the dominant crop in the Faguibine. The ethnic composition of the region is - as in the entire Sahel quite heterogeneous. Nomadic tribes such as the Tuareg and Maures (Tormoz) live with their slaves in the western parts and on the northern shore of the Lake, whilst the sedentary population (Songhay-Koiroboro) is settled in great clay-brick made villages on the southern shore. Those peasants who depend on the nomads (iklan and harratin) and the landholders of the Songhay aristocracy live in semi nomadic camps called debe which move within the Faguibine region according to the shifting of arable land. All agricultural work is done by the dependant slaves and land holders, who are generally not land-owners. The strong personal ties and solidarity structures between the landholders and the land owners proved to be an obstacle to any land reform. The chances of rural development seem to be quite limited because of the peripheral geographical position as well as lack of financing possibilities. The hydrological projects - planned during the last decade of the colonial era - to stabilize the Niger flood at the level of 265 m NN in order to gain sufficient arable land each year were never carried out; they also involve many social problems (the danger of land speculation, increasing usurping of land by functionaries and grain merchants from towns outside the Faguibine-region).